Union européenne et réseaux - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Dix-neuf réseaux opérant dans les pays membres de l'Association pour le renforcement de la recherche agricole en Afrique de l'Est et du Centre (Association for Strengthening Agricultural Research in Eastern and Central Africa, ASARECA) se sont...